EVALUATION OF THE DOMINANT PROTEIN FROM WHOLE-CELL HEATING METHOD USING MALDI-TOF/TOF MASS SPECTROMETRY - Gusti Ningrum, Siti; Wibawan, I Wayan Teguh (Journal of microbiology, biotechnology and food sciences, 2021)
Immunoglobulin G (IgG) are the essential tools in diagnostic kits. The whole-cell is still considered to be used for animal‘s immunization to produce IgG. The goal of this study was to determine dominant protein on the Shiga toxin-producing Escherichia coli (STEC) O157:H7-induced typical antibody response also determined by MALDI-TOF/TOF mass spectrometry. The heating method was conducted at 71 °C and 83 °C for antigen preparation. The proteins were characterized using SDS-PAGE and evaluated by MALDI-TOF/TOF mass spectrometry. The present study reported that the dominant polyclonal antibody inducing protein was ompC E. coli. The evaluation of mass spectra by MALDI-TOF/TOF might help to identify the dominant polyclonal antibody inducing protein in future preparation of diagnostic kits.